On universities' long-term effects on regional value creation and unemployment: The case of Germany - Henning Kroll; Torben Schubert (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
It is widely believed that universities exert notable effects on their regional socio-economic environment. So far, much of the empirical evidence supporting this claim is based on case studies. While such studies often give a detailed picture of the contributions of individual universities for their specific environments, almost no figures are available for effects of Higher Education Institutions (HEI) on the macroeconomic or economy-wide level. This paper seeks to fill this gap by using spatial panel-data models in order to identify the impact that HEIs have on value creation and unemployment in Germany. Other than prior studies, we do not seek to identify only direct effects (e.g. demand side effects caused by HEI investment) but we seek to identify the effects in terms of wider knowledge generation. Corresponding with this broad view we find evidence of strong effects on regions' GDP. HEIs contribute to Germany's GDP with exteuro 600bn per annum, i.e. about one fourth of the total value creation. 92% of this effect, however, is due to spillovers between regions. Thus the spatial distribution of the effects is rather flat. We also find that while in the short-run HEIs increase the unem-ployment rate, they lower it by on average 3.5% in the medium to long-run.
urn:nbn:de:0011-n-2868976
Keywords: 330